THE ROLE OF SHARI’A ACCOUNTING STANDARDS IN ORGANIZING AND GUIDING ISLAMIC FINANCIAL INSTITUTIONS - Mourad Mouloua; Antar Oukkal (International Journal of Innovative Technologies in Social Science, 2025)
This research aims to analyze Shari’a standards in Islamic financial accounting using a descriptive and analytical approach while examining the role and significance of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) in regulating Islamic financial institutions. Through an analysis of the theoretical frameworks and fundamental principles of Islamic accounting, we have assessed the impact of AAOIFI standards on transparency and governance in the sector. The findings indicate that the accountability of Islamic financial institutions is based on the application of Islamic accounting principles, ensuring the credibility of financial statements and the transparency of financial disclosures, thereby safeguarding the rights of all stakeholders. The rigorous application of Shari’a accounting standards contributes to a more efficient organization of Islamic financial institutions, strengthening their governance and the reliability of financial information.